INTEGRASI MEDIA DIGITAL DALAM PENDEKATAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP: TINJAUAN LITERATUR SISTEMATIS - Anggun Siska Hamidah; Retno Subekti; Zafrullah Zafrullah (Universitas HKBP Nommensen, 2026)
This study aims to examine the effectiveness of the Realistic Mathematics Education (RME) approach supported by digital media in enhancing junior high school students’ mathematical problem-solving skills, as well as to identify the types of digital media integrated into mathematics learning. This review was conducted as a systematic literature study following the PRISMA 2020 guidelines, including the stages of identification, screening, eligibility assessment and inclusion. A total of 147 articles were initially retrieved, of which 13 articles fulfilled the inclusion criteria and were analyzed comprehensively. The synthesis results indicate that the implementation of the RME approach consistently improves students' mathematical problem-solving skills. This improvement was reflected in higher post-test scores and better learning outcomes compared to conventional instruction. Various digital media, including as GeoGebra, VBA Excel, MathCityMap, Augmented Reality (AR), learning videos supported by Capcut, media 3D, E-Modul, Virtual Exhibition, Pixton, Live Worksheet, Quizizz, and E-Book assisted by Smart Apps Creator. These media support the exploration and visualization of mathematical concepts and facilitate interactive problem-solving activities. The integration of digital media within the RME approach is primarily focuses on understanding contextual problems, developing mathematical models, solving problems, and discussing solutions. Meanwhile, the use of digital media in the final stage, particularly in drawing conclusions and generalizing mathematical concepts, remains relatively limited. These findings emphasize that digital media integration can strengthen mathematics learning and make instruction more adaptive to the demands of 21st-century education. This study recommends further integration of digital media that can support reflection and generalize mathematical concepts in the final stage of the RME approach.